Residential mobility and neighbourhood attachment in Guangzhou, China. (May 2019) - Li, Si-ming; Mao, Sanqin; Du, Huimin
Wholesale redevelopment, suburbanization and increased population mobility in recent decades have brought significant social and spatial changes to urban neighbourhoods in Chinese cities, not least the subjective feelings of residents about their neighbourhoods. While there is a substantial literature on urban restructuring and migration at different geographical scales, relatively little is known about how feelings such as neighbourhood attachment are conditioned upon residential mobility and neighbourhood change in Chinese cities. To address this deficiency in the literature, multi-level models are employed to explore the extent to which residential mobility affects three different dimensions of neighbourhood attachment based on a large-scale household survey conducted in Guangzhou in 2012. The findings show that mobility experience and neighbourhood-related factors exert discernible influences on the attitudes towards the neighbourhood. Specifically, while people staying in reform/work-unit housing compounds tend to have better knowledge of their neighbours, those moving from reform/work-unit compounds to commodity housing estates exhibits greater involvements in the affairs of the new neighbourhood. The built environment, population size and frequency of population turnovers of the neighbourhood underpin residents' attachment to it.